Xây dựng qui trình phân tích một số Glucocorticoid ngụy tạo trong chế phẩm dược liệu bằng phương pháp UHPLC-UV-Vis / Trần Ngọc Luân, Đỗ Châu Minh Vĩnh Thọ, Nguyễn Đức Tuấn - Trần, Ngọc Luân
A simple reversed phase UHPLC-UV-Vis method was developed for simultaneous determination of prednisolone, methylprednisolone, betamethasone, and dexamethasone acetate adulterated in herbal medicines used for treatment of rheumatoid arthritis. The method was estalished as: Column - Thermo Acclamide Polar C16 (4.6 x 250 mm; 5µm); Mobile phase - acetonitrile and water in gradient mode; Flow rate - 1 ml/min; Detector – UV (240 nm). Validated in observane to the AOAC guidelines, the proposed method showed to meet well the all the requirements: suitability for UHPLC system, selectivity, linearity range (R2 > 0.995), accuracy (recoveries in the range of 90% - 107%), and precision (RSD < 5.3%), and high sensitivity (LOD: 0.32 ppm, LOQ: 1.3 ppm). For practical tets, these four glucocorticoids were analyized in 30 available herbal products; of these five were found illegally aldulterated with corticoids.